Determining toothache severity in pediatric patients: A study - Gupta V; Chandrasekar T; Ramani P; Anuja (Wolters Kluwer Medknow Publications, 2006)
To correlate sodium-potassium levels in saliva of pediatric patients having different intensities of toothache assessed by Visual Analogue Scale (VAS) in age group 3-14 yrs. A prospective study of 50 children having different intensities of pain was carried out in the Dept. of Pedodontics, Sareetha Dental College and Hospital. 50 children (aged 3-14 yrs) having different intensities of toothache including normal children (control) were included in the study. Saliva samples were collected and Na+, K+ levels in saliva were measured by using Na+, k+ colorimeter kit. Photographs were taken using Digital camera and VAS was prepared accordingly. Sodium levels decreased with increasing pain intensity and potassium levels increased, facial expressions correlated with Na+, K+ levels. Correlation between Na+, K+ levels and pain intensity exists. Also, VAS is a valid measure for pain.